The rise of techno-geopolitical uncertainty: Implications of the United States CHIPS and Science Act - Luo, Yadong; Van Assche, Ari (Journal of International Business Studies, 2023)
Growing techno-geopolitical uncertainty affects international business in many ways, calling for more scholarly attention to its causes and multinational enterprise (MNE) responses. The United States CHIPS and Science Act epitomizes the country’s recent embrace of techno-nationalism in its economic rivalry with China, which has major implications for IB scholarship and management practice. The Act exhibits two features that fly against America’s traditional liberal policy stance of championing an open and rules-based multilateral system. First, its reliance on subsidies, export control, and investment screening signifies departure from free trade and from market-based industrial policies. Second, its use of guardrail provisions pursues the weaponization of global value chains for geopolitical and geo-economic purposes. We view the Act as a showcase of a paradigm shift from market-oriented liberalism to intervention-oriented techno-nationalism, heralding a new era of zero-sum thinking and geopolitical prioritization. By examining the broader trend of techno-nationalism, we explore the distinct features of the Act and analyze the geo-strategies that MNEs need to adopt in response to the resulting techno-geopolitical uncertainty. Our analysis highlights the paradigm shift in policymaking, identifies the root causes of this shift, and examines the potential pitfalls it may create. To navigate this uncertain landscape, we suggest four strategic responses for MNEs: geo-strategies, reconfiguration, resilience, and corporate diplomacy.